The role of tech startups in the fight against COVID-19. Issue 1 (28th December 2020) - Almeida, Fernando
Abstract : Purpose: This study explores the contribution that tech startups can provide in the fight against COVID-19. The Tech4Covid movement is presented to that effect, which has joined several Portuguese tech startups. This initiative gathers more than 5, 000 volunteers and 28 ongoing projects in several interdisciplinary areas, including science, technology, health and education. Design/methodology/approach: Two qualitative methods are adopted: the case study and the field research technique. This joint approach allows exploring in-depth the relevance and impact of the different areas included in Tech4Covid movement. Data were collected both from primary sources, namely by the authors' participation in the movement and by the use of secondary sources from each project. Findings: The findings reveal three main areas in which the 28 ongoing projects can be categorized, respectively: support to health professionals and hospital equipment, health and education services and business and leisure. These projects offer direct and indirect contributions to the fight against COVID-19. From a perspective, they were initially designed to support health professionals in gathering protective equipment and supporting screening for suspicious cases. From another perspective, they also offer indirect benefits to citizens and the local economy. Originality/value: This paper addresses a recent phenomenon with a dramatic impact on public health, social and economic dimensions. The study provides essentially practical contributions by revealing how Portuguese technological startups were organized and worked together to respond to the COVID-19 pandemic. It is expected this study will serve as a reference for other countries and communities that intend to replicate this model.